Essays. - Lifshitz, Felice, 1959- author.
1 online resource.
Keywords: "Writing Normandy brings together eighteen articles by historian Felice Lifshitz, some of which are published here for the first time. The articles examine the various ways in which local and regional narratives about the past were created and revised in Normandy during the central Middle Ages. These narratives are analysed through a combination of both cultural studies and manuscript studies, in order to assess how they functioned, who they benefitted, and the various contexts in which they were transmitted. The essays pay particular attention to the narratives built around venerated saints and secular rulers, and in doing so bring together narratives that have traditionally been discussed separately by scholars. The book will appeal to scholars and students of cultural history and medieval history, as well as those interested in manuscript studies"--